Dental implant surface temperatures following double wavelength (2780/940 nm) laser irradiation in vitro - Peter Fahlstedt; Dagmar F Bunæs; Stein Atle Lie; Knut N Leknes (Wiley, 2021)
Abstract Objective To estimate the implant surface temperature at titanium dental implants during calibrated irradiation using double wavelength laser. Material and methods A double wavelength laser, 2780 nm Er,Cr:YSGG and 940 nm diode, was calibrated and used to irradiate pristine titanium dental implants, OsseoSpeed, TiUnite and Roxolid SLActive, representing different surface modifications. Initial calibration (21 implants; 7 implants/group) intended to identify optimal wavelength/specific output power/energy that not critically increased the temperature or altered the micro‐texture of the implant surface. Subsequent experimental study (30 implants; 10 implants/group) evaluated implant surface temperature changes over 190 s. Irradiation using a computerized robotic setup. Results Based on the initial calibration, the following output powers/energies were employed: Er,Cr:YSGG laser 18.4 mJ/pulse (7.3 J/cm2)-36.2 mJ/pulse (14.4 J/cm2) depending on implant surface; diode laser 3.3 W (1321.0 W/cm2). During double wavelength irradiation, implant surface temperatures dropped over the first 20 s from baseline 37°C to mean temperatures ranging between 25.7 and 26.3°C. Differences in mean temperatures between OsseoSpeed and TiUnite implants were statistically significant (p < 0.001). After the initial 20 s, mean temperatures continued to decrease for all implant surfaces. The decrease was significantly greater for TiUnite and Roxolid SLActive compared with OsseoSpeed implants (p < 0.001). Conclusion Calibrated double wavelength laser irradiation did not critically influence the implant surface temperature. During laser irradiation the temperature decreased rapidly to steady‐state levels, close to the water/air‐spray temperature.